The Mechanical and Tribology Properties of Sputtered Titanium Aluminum Nitride Coating on the Tungsten Carbide Insert Tool in the Dry Turning of Tool Steel - Budi, Esmar; bin Muhamad, Mohd. Razali; Rahman, Md. Nizam bin Abdul (UI Scholars Hub, 2014)
The effect of the sputtering parameters on the mechanical tribology properties of Titanium Aluminum Nitride coating on the tungsten cabide insert tool in the dry turning of tool steel has been investigated. The coating was deposited using a Direct Current magnetron sputtering system with various substrate biases (-79 to -221 V) and nitrogen flow rates (30 to 72 sccm). The dry turning test was carried out on a Computer Numeric Code machine using an optimum cutting parameter setting. The results show that the lowest flank wear ( 0.4 mm) was achieved using a Titanium Aluminum Nitride-coated tool that was deposited at a high substrate bias (-200 V) and a high nitrogen flow rate (70 sccm). The lowest flank wear was attributed to high coating hardness.